1997
DOI: 10.2337/diab.46.8.1305
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Requirement of Insulin Secretion Distal to Calcium Influx

Abstract: A number of agents that inhibit oxidative phosphorylation by different mechanisms (carbonyl cyanide mchlorophenylhydrazone [CCCP], sodium azide, oligomycin) induced an increase of cytoplasmic Ca2+ concentration ([Ca2+]i) in pancreatic beta-cells, as measured by microfluorimetry with digital imaging. All three agents are known inhibitors of insulin secretion, and the secretory response to 20 mmol/l glucose was found to be abolished in spite of elevated [Ca2+]i. Two reasons could account for this dissociation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Another possible explanation for the lack of effect of rotenone and oligomycin on cell‐attached K ATP channel activity is that these compounds are less effective at depleting intracellular levels of ATP than sodium azide. However, this seems unlikely as rotenone, oligomycin and sodium azide all produce comparable reductions in intracellular ATP levels ( Niki et al ., 1989 ; Rustenbeck et al ., 1997 ; Gribble et al ., 1997a ). It should be noted that recent evidence indicates that oligomycin fails to activate K ATP channels in pancreatic beta cells even though it significantly reduces ATP production ( Rustenbeck et al ., 1997 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible explanation for the lack of effect of rotenone and oligomycin on cell‐attached K ATP channel activity is that these compounds are less effective at depleting intracellular levels of ATP than sodium azide. However, this seems unlikely as rotenone, oligomycin and sodium azide all produce comparable reductions in intracellular ATP levels ( Niki et al ., 1989 ; Rustenbeck et al ., 1997 ; Gribble et al ., 1997a ). It should be noted that recent evidence indicates that oligomycin fails to activate K ATP channels in pancreatic beta cells even though it significantly reduces ATP production ( Rustenbeck et al ., 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this seems unlikely as rotenone, oligomycin and sodium azide all produce comparable reductions in intracellular ATP levels ( Niki et al ., 1989 ; Rustenbeck et al ., 1997 ; Gribble et al ., 1997a ). It should be noted that recent evidence indicates that oligomycin fails to activate K ATP channels in pancreatic beta cells even though it significantly reduces ATP production ( Rustenbeck et al ., 1997 ). Alternatively the metabolic source and/or site of ATP production may be important in CRI‐G1 insulinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The actions of imidazolines on pancreatic islets or single pancreatic B‐cells were investigated using the following techniques: measurement of insulin secretion of perifused mouse islets by radioimmunoassay, measurement of K ATP channel activity and membrane potential by patch‐clamping of single B‐cells, and measurement of cytoplasmic Ca 2+ concentration by microfluorimetry of single islet cells (refs. 12 and 21 and references therein).…”
Section: Methodsmentioning
confidence: 99%
“…Apparently, there are sites additional to K ATP channels where energy metabolism influences insulin secretion. 12 In addition, electrophysiologic experiments in which membrane capacitance was measured as an indicator of insulin secretion suggested that sulfonylureas may induce secretion by mechanisms other than closure of K ATP channels. Activation of protein kinase C was reported to play a decisive role, whereas Ca 2+ influx due to K ATP channel closure appeared only to be responsible for a minor part of the enhanced rate of secretion.…”
mentioning
confidence: 99%
“…2C is essential for the BBT-potentiated GSIS As reported, besides the cAMP/PKA pathway, Ca 2C -influxrelated signaling also functions potently in insulin secretion (Rustenbeck et al 1997 (Gomez et al 2002)) and thapsigargin (an inhibitor of…”
Section: Camentioning
confidence: 99%